Excitonic gap generation in thin-film topological insulators. (24th July 2017) - Menezes, Natália; Morais Smith, C; Palumbo, Giandomenico
Abstract: In this work, we analyze the excitonic gap generation in the strong-coupling regime of thin films of three-dimensional time-reversal-invariant topological insulators. We start by writing down the effective gauge theory in 2 + 1-dimensions from the projection of the 3 + 1-dimensional quantum electrodynamics. Within this method, we obtain a short-range interaction, which has the form of a Thirring-like term, and a long-range one. The interaction between the two surface states of the material induces an excitonic gap. By using the large- N approximation in the strong-coupling limit, we find that there is a dynamical mass generation for the excitonic states that preserves time-reversal symmetry and is related to the dynamical chiral-symmetry breaking of our model. This symmetry breaking occurs only for values of the fermion-flavor number smaller than N c ≈ 11.8 . Our results show that the inclusion of full dynamical interaction strongly modifies the critical number of flavors for the occurrence of exciton condensation, and therefore cannot be neglected.